Motivation Analysis and the Influence of Islamic Attributes on Muslim Tourists Satisfaction - Ariadi, Yudi; Suryadinata, Muh. Rifki; U, Ni Putu Ayu Chandra; Lestari, Imanda (PT FORMOSA CENDEKIA GLOBAL, 2025)
Muslim tourists are a new target along with the growth of the world's Muslim population. Halal tourism concept can be use to attract muslim tourists, by prioritizing Islamic attributes as a fulfillment of the special needs of Muslim tourists. This study aims to determine the motivation of tourists to travel including the influence of Islamic attributes on the satisfaction of Muslim tourists. This study was conducted using secondary data analysis, various literatures were used to support the research, the literature came from various sources, such as journals, theses, books, that related to tourist motivation, also research on the influence of the existence of Islamic attributes of tourist destinations on tourist satisfaction. Various data were also used to support this research from various websites and trusted institutions.